Immortalization of pancreatic stellate cells as an in vitro model of pancreatic fibrosis: deactivation is induced by matrigel and N-acetylcysteine - Jesenofsky, Ralf; Fürst, Daniel; Ringel, Jörg; Chen, Ying; Schrödel, Andrea; Kleeff, Jörg H.; Kolb, Armin; Schareck, Wolfgang; Löhr, J.-Matthias (Laboratory investigation, 2005)
Tissue fibrosis is one of the characteristics of chronic pancreatitis and pancreatic adenocarcinoma. Activated pancreatic stellate cells (PSC) play a central role in this process. However, analysis of the molecular mechanisms leading to PSC activation is hampered by the lack of an established human PSC line. To overcome this problem, we immortalized and characterized primary human PSC. The cells were isolated by the outgrowth method and were immortalized by transfection with SV40 large T antigen and human telomerase (hTERT). Primary human PSC served as controls. An immortalized line, RLT-PSC, was analyzed for the expression of stellate cell markers. Moreover, the effects of transforming growth factor β 1(TGFβ1) or platelet-derived growth factor stimulation and of cultivation on basement membrane components or N-acetylcysteine (NAC) treatment on gene and protein expression and proliferation were analyzed. Immortal RLT-PSC cells retained the phenotype of activated PSC proven by the expression of α-smooth muscle actin (αSMA), vimentin, desmin and glial fibrillary acidic protein (GFAP). TGFβ1 treatment upregulated the expression of αSMA, collagen type I (Col I), fibronectin and TGFβ1. Incubation of RLT-PSC cells and primary human activated PSC on Matrigel plus NAC treatment resulted in a deactivated phenotype as evidenced by a decrease of αSMA, connective tissue growth factor and Col I expression and by a decreased proliferation of the cells. Moreover, this treatment restored the ability of the cells to store vitamin A in cytoplasmic vesicles. In conclusion, we have established an immortal pancreatic stellate cell line, without changing the characteristic phenotype. Importantly, we were able to demonstrate that besides soluble factors, the matrix surrounding PSC plays a pivotal role in the maintenance of the activation process of PSC. Cultivation of activated PSC on a reconstituted basement membrane plus treatment with NAC was able to deactivate the cells, thus pointing to the possibility of an antifibrosis therapy in chronic pancreatitis.
Gesehen am 24.05.2022